2013
DOI: 10.5539/emr.v3n1p8
|View full text |Cite
|
Sign up to set email alerts
|

A Conservation of Resources Approach to Blackberry Use, Work-Family Conflict and Well-Being: Job Control and Psychological Detachment from Work as Potential Mediators

Abstract: This paper provides a comparison study of the relationships between using the Blackberry (BB) device for work purposes during non-work hours and (a) work-family conflict and (b) well-being, and the potential mediators of these relationships from a Conservation of Resources (COR) approach. Findings revealed that greater usage of the BB for work purposes during non-work hours was related to higher levels of work-family conflict. In particular greater frequency of use was related to an inability to psychologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 48 publications
2
30
0
2
Order By: Relevance
“…In line with previous research on psychological detachment (Sonnentag and Fritz 2015), failing to switch off during non-work time is further associated with reduced well-being (Derks et al 2014b;Richardson 2010;Ward and Steptoe-Warren 2014). In addition to affecting well-being, a lack of psychological detachment due to voluntary ICT use has also been associated with work-life conflict (Richardson and Thompson 2012;Ward and Steptoe-Warren 2014), where employees endeavour simultaneously to work and engage in non-work activities, such as dinner with family, but only give partial attention to the non-work activity, which is noticed and reproached by family members (Ladner 2008;Voydanoff 2005). We thus propose psychological detachment as another potential mechanism through which voluntary ICT use affects work-life conflict and, subsequently, well-being.…”
Section: Designated Non-work Time and Well-beingsupporting
confidence: 77%
See 3 more Smart Citations
“…In line with previous research on psychological detachment (Sonnentag and Fritz 2015), failing to switch off during non-work time is further associated with reduced well-being (Derks et al 2014b;Richardson 2010;Ward and Steptoe-Warren 2014). In addition to affecting well-being, a lack of psychological detachment due to voluntary ICT use has also been associated with work-life conflict (Richardson and Thompson 2012;Ward and Steptoe-Warren 2014), where employees endeavour simultaneously to work and engage in non-work activities, such as dinner with family, but only give partial attention to the non-work activity, which is noticed and reproached by family members (Ladner 2008;Voydanoff 2005). We thus propose psychological detachment as another potential mechanism through which voluntary ICT use affects work-life conflict and, subsequently, well-being.…”
Section: Designated Non-work Time and Well-beingsupporting
confidence: 77%
“…However, the decrease in perceived flexibility and control has also been reported by employees (Crowe and Middleton 2012;Quesenberry and Trauth 2005). Evidence in quantitative research was similarly mixed when examining perceived control as consequence of voluntary ICT use: whereas one study found partial support for the positive association between voluntary ICT use and perceived job control (Richardson and Thompson 2012), several studies did not find an association (Duxbury et al 1996;Richardson 2010;Ward and Steptoe-Warren 2014).…”
Section: Job-related Characteristics and Work Processesmentioning
confidence: 89%
See 2 more Smart Citations
“…Of the 110 participants that were included in the final dataset, 48.2% were international 3 The outlier-labeling rule can be used to identify outliers for normal-distribution data. Prior studies have relied on this technique to identify outliers (Huian, 2015;Ward and Steptoe-Warren, 2013). The outlier-labeling rule is based on finding the difference between the first and third quartile of the distribution and multiplying it by a parameter, g, which is equal to 2.2 (see Hoaglin et al, 1986;Hoaglin and Iglewicz, 1987).…”
Section: Participantsmentioning
confidence: 99%